Influential Article Review - Is There a Migratory Effect? On Opinions Regarding Government Accountability, Russian Migrant Communities in Western Europe Are Compared to Russians in Three Former Soviet Nations - Pena, Zayne; Murillo, Aron; Horner, Aniyah (Journal of Management Policy and Practice, 2021)
This paper examines migration. We present insights from a highly influential paper. Here are the highlights from this paper: In a number of recent articles migration has been used as a ‘natural experiment’, which can give insights into the general mechanisms of attitude formation. Studies from the field of psychology, however, suggest that the process of acculturation might be affected by migrants being in a particular situation. If such a ‘migration effect’ exists, then the conclusions on the more general mechanisms of attitude formation based on migration studies have to be rethought. We test this using a novel study design comparing acculturation in which we compare attitudes in the Russian diaspora left behind, in Estonia, Latvia and the Ukraine, by the collapse of the Soviet Union to those of Russian migrants in Germany, Denmark and the Netherlands. The results show that there are no differences in acculturation between the diaspora in the East and the migrants in the West and therefore no ‘migration effect’ on acculturation. For our overseas readers, we then present the insights from this paper in Spanish, French, Portuguese, and German.